SNPversity: a web-based tool for visualizing diversity. (20th April 2018) - Schott, David A; Vinnakota, Abhinav G; Portwood, John L; Andorf, Carson M; Sen, Taner Z
Abstract: Many stand-alone desktop software suites exist to visualize single nucleotide polymorphism (SNP) diversity, but web-based software that can be easily implemented and used for biological databases is absent. SNPversity was created to answer this need by building an open-source visualization tool that can be implemented on a Unix-like machine and served through a web browser that can be accessible worldwide. SNPversity consists of a HDF5 database back-end for SNPs, a data exchange layer powered by TASSEL libraries that represent data in JSON format, and an interface layer using PHP to visualize SNP information. SNPversity displays data in real-time through a web browser in grids that are color-coded according to a given SNP's allelic status and mutational state. SNPversity is currently available at MaizeGDB, the maize community's database, and will be soon available at GrainGenes, the clade-oriented database for Triticeae and Avena species, including wheat, barley, rye, and oat. The code and documentation are uploaded onto github, and they are freely available to the public. We expect that the tool will be highly useful for other biological databases with a similar need to display SNP diversity through their web interfaces. Database URL : https://www.maizegdb.org/snpversity